Expression of hemolysins in vivo and role of HlyBA in an intra-abdominal infection model - Lobo, Leandro A.; Jenkins, Audrey L.; Jeffrey Smith, C.; Rocha, Edson R. (My University, 2013)
Bacteroides fragilis is the most frequent opportunistic pathogen isolated from anaerobic infections. However, there is a paucity of information regarding the genetic and molecular aspects of gene expression of its virulence factors during extra-intestinal infections. A potential virulence factor that has received little attention is the ability of B. fragilis to produce hemolysins. In this study, an implanted perforated table tennis “ping-pong” ball was used as an intra-abdominal artificial abscess model in the rat. This procedure provided sufficient infected exudate for gene expression studies in vivo. Real-time reverse transcription polymerase chain reaction (RT-PCR) was used to quantify the relative expression of hlyA, hlyB, hlyC, hlyD, hlyE, hlyF, hlyG, and hlyIII mRNAs. The hlyA mRNA was induced approximately sixfold after 4 days postinfection compared with the mRNA levels in the inoculum culture prior to infection. The hlyB mRNA increased approximately sixfold after 4 days and 12-fold after 8 days postinfection. Expression of hlyC mRNA increased sixfold after 1 day, 45-fold after 4 days, and 16-fold after 8 days postinfection, respectively. The hlyD and hlyE mRNAs were induced approximately 40-fold and 30-fold, respectively, after 4-days postinfection. The hlyF expression increased approximately threefold after 4-days postinfection. hlyG was induced approximately fivefold after 4 and 8 days postinfection. The hlyIII mRNA levels had a steady increase of approximately four-, eight-, and 12-fold following 1, 4, and 8 days postinfection, respectively. These findings suggest that B. fragilis hemolysins are induced and differentially regulated in vivo. Both parent and hlyBA mutant strains reached levels of approximately 3–8 × 109 cfu/mL after 1 day postinfection. However, the hlyBA mutant strain lost 2 logs in viable cell counts compared with the parent strain after 8 days postinfection. This is the first study showing HlyBA is a virulence factor which plays a role in B. fragilis survival in an intra-abdominal abscess model.
Keywords: Anaerobic infection; Bacteroides fragilis; experimental intra-abdominal infection; hemolysins; in vivo gene expression